Nonlinear optical properties of polymer [PMMA] thin films doped with dye lasing compounds, Rhodamine 6G and Acriflavine in chloroform solvent by using dip coating method - Omar Shaker Shafeeq (Iraqi Journal of Physics, 2018)
The fluorescence emission of Rhodamine 6G (R6G) and Acriflavine dyes in PMMA polymer have been studied by changing the irradiation and exposure time of laser light to know the effect of this parameter. It was found that the fluorescence intensity decreases in the polymer samples doped dyes as the exposure time increases and then reaches stabilization at long times, this behavior called photobleaching, which have been shown in liquid phase less than solid phase. Using 2nd harmonic with wavelength 530 nm laser, the photobleaching effect in the two dye-doped polymers different solvent but same was studied. It was observed that photobleaching of by different solution and by using dip spin coating the photobleaching seem in liquid phase more than the thin films from the mixing solutions with a thickness of (0.1 to 1 micrometer). The maximum peak of fluorescence seems as red shift with different solvent concentration.